The incentive structure of the originate-to-distribute model of lending, bank credit supply and risk taking behaviour of U.S. commercial banks - Chen, Conghui (2015)
The Originate-to-distribute (OTD) model allows banks to sell or securitize loans rather than holding them until maturity. We investigate the incentives for using OTD lending and its impact on credit supply and bank risk taking behavior based on their involvements in the OTD model and bank size. Banks involved into OTD lending have more OTD loans and riskier mortgage portfolios. Funding cost reduction and liquidity needs are more important for high-OTD banks and small banks and regulatory capital arbitrage can only be found in small banks. Moreover, we find that OTD lending increase credit supply, but it has adverse effect on bank risk, especially for small banks involved in the model.